1999
DOI: 10.1002/(sici)1099-0690(199907)1999:7<1527::aid-ejoc1527>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mesogenic Properties of Porphyrin Octaesters

Abstract: A new and efficient method of preparing 3,4-pyrrolediacetic diffraction, and miscibility tests. The planarity of the macrocyclic core constitutes the major structural requirement esters 3 is reported, together with their conversion, according to the Lindsey procedure, to a series of octa-and dodeca-for mesophase formation. The mesophase temperature range is controlled by the length of the side chains through the substituted porphyrins. This procedure, which consists of a palladium-catalysed oxidative alkoxycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
1
16
0
1
Order By: Relevance
“…The initial experiments afforded compounds 84, 96 but it was later found that they could be isomerized in situ to the corresponding pyrroles by using dimethylacetamide (DMA) as cosolvent (Scheme 68). 97…”
Section: Methods Based On Palladium-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
“…The initial experiments afforded compounds 84, 96 but it was later found that they could be isomerized in situ to the corresponding pyrroles by using dimethylacetamide (DMA) as cosolvent (Scheme 68). 97…”
Section: Methods Based On Palladium-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
“…1) [36]. Condensation of the resulting compound with paraformaldehyde in the presence of boron trifluoride etherate gave octasubstituted porphyrins.…”
Section: Synthesis Of Porphyrin Precursorsmentioning
confidence: 99%
“…In 1994, 5,15-disubstituted porphyrin, a rod-like liquid crystal, was synthesized by Bruce [5] and a temperature of liquid crystal phase change was 298℃. In 1989, Kubota [6] first used porphyrin liquid crystal for color display, and Yamamoto [7] made a display device using benzoporphyrin liquid crystal in 1990 and applied for a patent. We have studied the liquid crystalline behavior [8] of meso-tetrakis-(4-noyloxy phenyl) porphyrin and its Zn complex.…”
Section: Introductionmentioning
confidence: 99%